The use of intuitive and analytic reasoning styles by patients with persecutory delusions. - Freeman, D; Lister, R; Evans, N (Elsevier, 2014)
BACKGROUND AND OBJECTIVES: A previous study has shown an association of paranoid thinking with a reliance on rapid intuitive ('experiential') reasoning and less use of slower effortful analytic ('rational') reasoning. The objectives of the new study were to replicate the test of paranoia and reasoning styles in a large general population sample and to assess the use of these reasoning styles in patients with persecutory delusions. METHOD: 30 Patients with persecutory delusions in the context of a non-affective psychotic disorder and 1000 non-clinical individuals completed self-report assessments of paranoia and reasoning styles. RESULTS: The patients with delusions reported lower levels of both experiential and analytic reasoning than the non-clinical individuals (effect sizes small to moderate). Both self-rated ability and engagement with the reasoning styles were lower in the clinical group. Within the non-clinical group, greater levels of paranoia were associated with lower levels of analytic reasoning, but there was no association with experiential reasoning. LIMITATIONS: The study is cross-sectional and cannot determine whether the reasoning styles contribute to the occurrence of paranoia. It also cannot be determined whether the patient group's lower reasoning scores are specifically associated with the delusions. CONCLUSIONS: Clinical paranoia is associated with less reported use of analytic and experiential reasoning. This may reflect patients with current delusions being unconfident in their reasoning abilities or less aware of decision-making processes and hence less able to re-evaluate fearful cognitions. The dual process theory of reasoning may provide a helpful framework in which to discuss with patients decision-making styles.